2013
DOI: 10.4103/0976-9668.107286
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of postoperative analgesic efficacy of transversus abdominis plane block after abdominal surgery: A comparative study

Abstract: Background:The transversus abdominis plane (TAP) block is an effective method of providing postoperative analgesia in patients undergoing midline abdominal wall incisions, by blocking the abdominal wall neural afferents via the bilateral lumbar triangles of Petit. We evaluated its analgesic efficacy in patients during the first 48 postoperative hours after abdominal surgery, in a randomized, controlled single-blind clinical trial.Materials and Methods:Sixty patients (mean age 36.2 ± 9.6 years) of either sex of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 9 publications
(12 reference statements)
3
20
0
1
Order By: Relevance
“…Effective postoperative pain treatment reduces surgical stress and plays a direct role in morbidity (6). Furthermore, prevention of respiratory depression due to early patient mobilization and pain affects postoperative respiratory functions positively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective postoperative pain treatment reduces surgical stress and plays a direct role in morbidity (6). Furthermore, prevention of respiratory depression due to early patient mobilization and pain affects postoperative respiratory functions positively.…”
Section: Discussionmentioning
confidence: 99%
“…Sharma et al(6) compared the analgesic effects of tramadol PCA and TAP block performed in addition to PCA, and they revealed that VAS values were lower in patients undergoing TAP block than in patients not undergoing TAP block.…”
mentioning
confidence: 99%
“…To clarify these data, comparative studies between the epidural technique and new anesthetic techniques would be necessary, which is what we are currently undertaking. For example, several studies supporting TAP block as an analgesic technique in colorectal surgery have been published (30,31). Our study has some limitations.…”
Section: Discussionmentioning
confidence: 87%
“…Other complications include urinary retention (28) or direct spinal cord injuries. For this reason, several studies advocate for other analgesic techniques (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Al ser un anestésico local de vida media, su inicio de acción una es de 30 minutos luego de ser colocada, presenta una vida media de 5 a 10 horas, razones por la cuales posee mayor tiempo de latencia y duración terapéutica mayor 17. La concentración mínima para obtener un efecto de bloqueo nervioso periférico es de 0,25%, sin embargo se recomienda una concentración de 0.5% para obtener mayor biodisponibilidad y efecto terapéutico 18 . Al colocarse la bupivacaína en el plano transverso del abdomen provee de anestesia a la piel, tejido celular subcutáneo músculo y peritoneo parietal, anatómicamente este se caracteriza por ser una zona pobremente vascularizada lo cual permite que la absorción del anestésico local sea más lenta, prolongando su efecto farmacológico y bloqueo nervioso sensitivo más prolongado en los nervios intercostales torácicos y primer lumbar 19 .…”
Section: Discussionunclassified